The indirect impact of the technostress subfactors on the satisfaction and desire to work from home - Simon, Adél Csenge; Buzás, Barnabás; Rosta-Filep, Orsolya; Faragó, Klára; Pachner, Orsolya Csilla; Kiss, Orhidea Edith (Frontiers in Psychology, 2024)
Introduction Organizational digitalization is a phenomenon that is becoming more widespread and holistic; that is responsible for more employees being affected by digital work and working from home. While introducing remote work offers numerous economic benefits for organizations, this transition must be aligned with employees' needs rather than in an authoritarian manner. Our research aimed to investigate how sub-factors of technostress, directly and indirectly, influence the satisfaction and desire to work from home. Methods We conducted a cross-sectional survey with a sample of 361 office workers with at least two years of experience who have spent some time working from home. We checked our hypotheses with a path model. Results Our research found that techno-insecurity and techno-complexity have a minimal direct influence on the desire to work from home. However, the desire to work from home significantly decreases through various mediation pathways via the status sub-factor (which can be seen as one of the latent benefits of remote work) and through satisfaction with working from home. Our model explains 33.7% of the variance in the desire to work from home. Discussion This suggests that leaders have a task of great significance: to decrease the technostress employees are exposed to and to draw the attention of researchers to the fact that technostress has more complex indirect effects than previously assumed.